2018
DOI: 10.1016/j.beproc.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical choice in rats: Subjective valuation and mechanism of choice

Abstract: Decision-makers benefit from information only when they can use it to guide behavior. However, recent experiments found that pigeons and starlings value information that they cannot use. Here we show that this paradox is also present in rats, and explore the underlying decision process. Subjects chose between two options that delivered food probabilistically after a fixed delay. In one option ("info"), outcomes (food/no-food) were signaled immediately after choice, whereas in the alternative ("non-info") the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
36
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 24 publications
7
36
5
Order By: Relevance
“…It could be that the trial-based, forced choice structure of many tasks forces the apparent direct trade-off between exploration and exploitation. Our results suggest that the decision-making processes that arbitrate exploration and exploitation may not inherently be in competition; rather, they may run in parallel with action selection arising from the winning decision made 47 . This is analogous to the current understanding of goal-directed and habitual action control systems as parallel processes, either of which may contribute to action control at a given time point 15 .…”
Section: Discussionmentioning
confidence: 87%
“…It could be that the trial-based, forced choice structure of many tasks forces the apparent direct trade-off between exploration and exploitation. Our results suggest that the decision-making processes that arbitrate exploration and exploitation may not inherently be in competition; rather, they may run in parallel with action selection arising from the winning decision made 47 . This is analogous to the current understanding of goal-directed and habitual action control systems as parallel processes, either of which may contribute to action control at a given time point 15 .…”
Section: Discussionmentioning
confidence: 87%
“…The results demonstrated that differences in discrimination performance were primarily influenced by cage and not by cohort (Nachev, in prep.). Thus, the sound cue associated with reward delivery may be an important confounding factor in probability discrimination in mice, as it provides a signal for the reward outcome (Ojeda, Murphy, and Kacelnik 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It provides a unique perspective on many aspects of economic choice and has recently come to influence the neuroscience and psychology of decision-making (Pearson et al 2014; Calhoun and Hayden 2015; Mobbs et al 2018; Hayden et al, 2011). A core idea in foraging theory is that natural decisions are fundamentally structured around accepting vs. rejecting – taking or passing up a single option that is the sole or primary focus of attention (Shapiro et al 2008; Vasconcelos et al 2010; Kacelnik et al 2011; Pirrone et al 2017; Ojeda et al 2018). Even ostensibly binary economic choices, in this view, reflect a pair of (potentially interacting) accept-reject choices.…”
Section: Introductionmentioning
confidence: 99%